Individual Rights (of a Person) Are Threatened When Maintaining Sustainable Stability of Life - Arianti, Farida; Febriyanti , Siska; Silvianetri; Al-Hakim, Sofian; Fikri, M Ihsanul (Institut Agama Islam Negeri Curup, 2025)
Individual/family rights, when not fulfilled, will bring about ongoing threats to life safety. Eliminating wealth/property leads to the pinnacle of poverty, a lack of prosperity, and dependence on others. This study aims to examine the rights of individuals/families regarding the lack of obligation to distribute consumed wealth as a threat to their lives. It also examines the causes of this lack of obligation to distribute consumed wealth. This study relies on a qualitative approach, with the type of field research, by collecting data through in-depth interviews with key informants and conducting observations. Data sources Datuak, Ninik mamak, bundo kandung, Minangkabau indigenous people. Analysis method with qualitative description. The research results show that the lack of utilization in asset distribution indicates the emergence of a form of difficulty in fulfilling individual/family rights to sustainability and survival. There are shortages in education, health, economic capital, and so on. The existence of Rangkiang values ​​is already feared, leading to the building being neglected and left to fall into disrepair, even though the building holds valuable value in the process of sustaining life. This paper concludes that a stable pattern of wealth consumption is associated with a person's fair attitude in balancing individual (self)/family rights and obligations in Hifzul Maal (preservation of wealth). Individual (self)/family rights are threatened when individual/family obligations in the distribution and consumption of wealth are neglected. The lack of sufficient living conditions has led to suffering due to the lack of everything needed to achieve life's activities.